The effect of economic development, income inequality and banking sector development on environmental quality: Empirical evidence in Indonesia - Jenni Irene; Fadli Septianto; Rossalina Christanti; Wahyu Trinarningsih (Sebelas Maret Business Review, 2024)
Our research explores how government expenditure, inequality, and bank lending could impact environmental quality. We assess the quality of the environment by utilizing the Environmental Quality Index, as supplied by the Ministry of Environment and Forestry. We use annual regional-level data from 2012 to 2021 gathered from the Indonesia Statistics Bureau (Badan Pusat Statistik-BPS), Bank Indonesia, and the environment reports of Indonesia provided by the Ministry of Environment and Forestry. Our final sample consists of 34 provinces across Indonesia. We use the human development index, the Indonesia democracy index, and the Gini index provided by the Indonesia Statistics Bureau to measure inequality. We use regional-level bank loan data provided by Bank Indonesia to measure bank lending. Lastly, we measure government expenditure using regional government expenditure data. This study uses the random effect model to estimate the empirical model. Hausman test is conducted to determine which model is appropriate between the fix and random effect models. These results imply that banking sector development, economic development proxied by government expenditure, and inequality proxied by the human development index and Indonesia democratic index negatively impact the environmental quality. Derived from the findings of the regression test, the overall expenditure at the regional level demonstrates a detrimental effect on environmental health. This is evident in the developmental trajectory of the state government, which has yet to be oriented towards environmental concerns. This is also supported by the results of subsample tests, which show that this linkage significantly affects regions with high inequality.